Legal Review Of The Determination Of Child Custody Rights After Divorce From The Perspective Of Indonesian Civil Law - Syna Ardia Putri Lubis; Bambang Fitrianto; Asman Siagian (JURNAL HUKUM SEHASEN, 2026)
The determination of child custody rights after divorce is an important issue in family law in Indonesia because divorce can have an impact on the mental condition and growth and development of children. Therefore, clear regulations are needed to ensure that children's rights are protected. This study aims to analyze the determination of child custody after divorce based on the perspective of Indonesian civil law and the forms of legal protection provided to children. The research method used is normative juridical, examining relevant legislation, doctrine, and legal literature. The results of the study show that the determination of child custody is not only based on the biological relationship between parents and children, but also prioritizes the principle of the best interests of the child. These provisions are regulated in Law Number 1 of 1974 concerning Marriage, Law Number 23 of 2002 in conjunction with Law Number 35 of 2014 concerning Child Protection, and the Compilation of Islamic Law (KHI). Even in the event of divorce, both parents remain obligated to care for, educate, and provide for the child. Legal protection of children encompasses all activities to guarantee and protect children and their rights so that they can live, develop, and grow properly and receive protection from violence and discrimination. Legal protection for children is all activities to guarantee and protect children and their rights so that they can live, develop, and grow properly, and receive protection from violence and discrimination. Child protection in the event of parental divorce is closely linked to the parents' authority, even if the marriage ends due to divorce initiated by both parents. Therefore, legal protection for children after divorce is not solely the responsibility of one parent, but rather of both parents, the father and mother of their children. The state also has a responsibility through the courts to provide legal certainty and guarantee the future of children so that they do not become victims of their parents' divorce.